REVALUATION AND DEPRECIATION OF PLANT ASSETS. - Kempner, Jack J. (The Accounting Review, 1952)
Abstract It is the purpose of this article to explore some of the factors which tie us to the historic basis of cost, and which inhibit all but the very bold from advocating current values along with a concrete plan for carrying their theory into effect. For a good many years from now, perhaps it might be safe to say several decades; most accounting authorities have been against the revaluation of plant assets. Cost or its equivalent has been the time-honored basis for the valuation of fixed assets on the balance sheet. On the other hand, there is no denying that there have been and are outstanding men in the profession who recognize the need for some sort of revaluation under certain conditions. Yet it is the author's impression that very few will ever give their unequivocal endorsement to any basis but cost. This apparent hedging may be due to the fact that no satisfactory substitute has yet been found to replace the cost theory. Also in all references to plant assets, the author has deliberately ignored land or its related natural resources. Revaluations of these assets are necessary in order to give a true picture of the enterprise. For these reason the above assets usually require separate treatment from the so-called man-made possessions.